Análise da sensibilidade dos componentes da equação de Hargreaves - Samani para a região de Bebedouro - SP - Palaretti, Luiz Fabiano [UNESP]; Mantovani, Everardo Chartuni; Sediyama, Gilberto Chohaku (Sociedade Brasileira de Meteorologia, 2014)
The estimation of reference evapotranspiration (ETo) subsidizes the calculations of water consumption in irrigated agriculture. The use of simpler methodologies are common however should be carefully studied. The present study evaluated the sensitivity of the Hargreaves -Samani equation compared to the standard Penman-Monteith -FAO to estimate ETo for the climatic conditions of the Bebedouro-SP region, simulating the effects of increasing and decreasing 5 % in the temperatures, resulting in ten different scenarios (PM -Penman-Montheit -FAO; S0 -original Hargreaves Samani; S1 to S8 -modified Hargreaves Samani). The obtained results of sensitivity, linear regression, accuracy and concordance index, were compared. We concluded that the Hargreaves -Samani equation overestimates the monthly values of the ETo in 13% compared to the standard method. A variation of 5% in maximum and minimum temperatures resulted in errors of up to 1 mm day-1 (monthly average) and this increase is more expressive in maximum temperature.

A estimativa da evapotranspiração de referência (ETo) subsidia os cálculos de consumo de água na agricultura irrigada. O uso de metodologias mais simples são comuns, porém devem ser criteriosamente estudadas. No presente estudo avaliou-se a sensibilidade da equação de Hargreaves - Samani frente ao padrão Penman-Monteith - FAO, na estimativa da ETo, para as condições climáticas da região de Bebedouro-SP, simulando os efeitos de acréscimos e decréscimos de 5% nas temperaturas, resultando em dez cenários distintos (PM - Penman-Montheit - FAO; S0 - Hargreaves Samani original; S1 à S8 - Hargreaves Samani - com alterações). Os resultados foram comparados em sensibilidade, por regressão linear, precisão e o índice de concordância. Conclui-se que a equação de Hargreaves - Samani superestima valores mensais de ETo em 13% comparado ao método padrão. Uma variação de 5% nas temperaturas máximas e mínimas resultaram em erros de até 1 mm dia-1, sendo o acréscimo mais expressivo na temperatura máxima.
Sensitivity analysis of Hargreaves Samani equation components for Bebedouro region - SP
Keywords: Irrigation; water consumption; Penman-Monteith; citrus crop; Irrigação; consumo de água; Penman-Monteith; Citros